Role of angiotensin-signalling in anthracycline-induced cardiotoxicity. (25th November 2020) - Findlay, S; Gill, J.H; Plummer, R; Plummer, C.J
Abstract: : Anthracycline chemotherapy remains a key component of cancer treatment regimens in both paediatric and adult patients. A significant issue with their use is the development of anthracycline-induced cardiotoxicity (AIC), with subclinical AIC and clinical heart failure observed in 13.8% and 3.1% of patients, respectively. The major clinical complication of AIC is the development of late-onset cardiotoxicity, occurring several years after drug administration, presenting as life-threatening heart failure (HF). Determining the relationship between subclinical AIC and late-onset HF, strategies for mitigation of AIC, and impacts upon the cancer survivor population remains a complex challenge. Administration of drugs targeting the angiotensin system, specifically angiotensin converting enzyme inhibitors (ACEi), have been reported to reduce AIC in the clinic. Whilst the therapeutic effect of ACEi in management of left ventricular systolic dysfunction and consequent HF is principally through optimisation of cardiac haemodynamics, the mechanism involved with mitigation of late-onset AIC several years after anthracycline exposure are currently unknown. Using a variety of human cardiomyocyte in vitro models we have previously demonstrated induction of cardiomyocyte hypertrophy by angiotensin II and anthracyclines. Importantly, selective blockade of the angiotensin II receptor 1 (ATR1) on cardiomyocytes mitigated the anthracycline-induced hypertrophic response, implicating synergism between AIC and angiotensin signalling in cardiomyocytes. Adult human ventricular cardiac myocyte AC10 cell-line were treated in vitro with a range of clinically relevant doxorubicin doses for clinically appropriate durations, with AT1 receptor gene expression evaluated using semi-quantitative PCR. Our results confirm a positive correlation between clinically-relevant concentration of doxorubicin and induction of genetic expression of ATR1 in AC10 cells, with up to 200% increases in ATR1 expression observed. Maximal doxorubicin-induced gene expression being observed at 8 and 24-hours, respectively. These preliminary results agreeing with clinical exposure parameters for this drug with protein expression studies being optimised to support these gene expression study results. Our preliminary studies also imply patients developing AIC carry a deleted polymorphism within intron 16 of the ACE gene and increased systemic levels of the ACE product angiotensin II, both with a known association to hypertrophic cardiomyopathy. Taken together, these data support our mechanistic hypothesis that a relationship exists between AIC and modulation of the angiotensin signalling pathway in cardiomyocytes, involving structural cellular changes and asymptomatic cardiac hypertrophy. An elevation in angiotensin II levels, potentially through polymorphisms in ACE, could thereby exacerbate anthracycline-induced hypertrophy and promote the development of late-onset anthracycline-induced HF. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Cancer Research UK funded PhD